2021
DOI: 10.1186/s12883-021-02512-1
|View full text |Cite
|
Sign up to set email alerts
|

Persistent hyperglycemia is a useful glycemic pattern to predict stroke mortality: a systematic review and meta-analysis

Abstract: Background Glycemic patterns have been reported to be prognostic factors for stroke; however, this remains to be further evaluated. This meta-analysis aimed to evaluate the usefulness of glycemic patterns such as persistent hyperglycemia (PH) including short duration and long duration PH (SPH; LPH), admission hyperglycemia (AH), short-duration hyperglycemia (SH), and persistent normoglycemia (PN) in predicting stroke prognosis using published results. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
(57 reference statements)
1
7
0
Order By: Relevance
“…First, the influence of elevated BG has not been fully elucidated. Previous literature has examined the impact of hyperglycemia on poor prognosis in different critically ill patients, such as those with myocardial infarction (7), acute pancreatitis (8), and stroke (9). However, these connections are not consistent across sepsis patients.…”
Section: Introductionmentioning
confidence: 99%
“…First, the influence of elevated BG has not been fully elucidated. Previous literature has examined the impact of hyperglycemia on poor prognosis in different critically ill patients, such as those with myocardial infarction (7), acute pancreatitis (8), and stroke (9). However, these connections are not consistent across sepsis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycaemia is present in 30-40% of people with acute ischaemic stroke, even without a history of diabetes (7,9). However, randomized clinical trials failed to show a bene t from intensive glucose control acutely (up to 72 hours) after stroke (12).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia is one of the hallmarks of T2D. In stroke patients (with or without diabetes), hyperglycaemia at admission is associated with poor outcome (9)(10)(11) and to date, interventional studies have been mainly focused on controlling hyperglycaemia acutely after hospitalization. However, the results of these studies showed no clinical bene t (12) suggesting that other underlying pathophysiological mechanisms of diabetes may be responsible of poor stroke recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia is one of the hallmarks of T2D. In stroke patients (with or without diabetes), hyperglycemia at admission is associated with a poor outcome [ 9 , 10 , 11 ] and, to date, interventional studies have been mainly focused on controlling hyperglycemia acutely after hospitalization. However, the benefit of treating hyperglycemia after stroke remains elusive, and intensive glucose control has shown no additional clinical benefit compared to standard in-hospital glycemic control [ 12 ], suggesting that other underlying pathophysiological mechanisms of diabetes may be responsible for poor stroke recovery.…”
Section: Introductionmentioning
confidence: 99%